Algebraic Aspects of the Advanced Encryption Standard - Cid, Carlos; Murphy, Sean.; Robshaw, Matthew; SpringerLink (Online service) (Boston, MA : Springer US, 2006)
The Belgian block cipher Rijndael was chosen in 2000 by the U.S. government$1 (Bs National Institute of Standards and Technology (NIST) to be the successor to the Data Encryption Standard. Rijndael was subsequently standardized as the Advanced Encryption Standard (AES), which is potentially the world$1 (Bs most important block cipher. In 2002, some new analytical techniques were suggested that may have a dramatic effect on the security of the AES. Existing analytical techniques for block ciphers depend heavily on a statistical approach, whereas these new techniques are algebraic in nature. Algebraic Aspects of the Advanced Encryption Standard, appearing five years after publication of the AES, presents the state of the art for the use of such algebraic techniques in analyzing the AES. The primary audience for this work includes academic and industry researchers in cryptology; the book is also suitable for advanced-level students.s
to the AES -- Mathematical Background -- Description of the AES -- Algebraic Properties of the AES -- Equation Systems for the AES -- Analysis of AES Equation Systems -- Closing Remarks.
Keywords: Computer science; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Computer science -- Mathematics; Algebraic geometry; Computer Science; Data Encryption; Data Structures, Cryptology and Information Theory; Algebraic Geometry; Coding and Information Theory; Math Applications in Computer Science; Electronic books